Differential effects of plant root systems on nickel, copper and silver bioavailability in contaminated soil. (February 2017) - Nguyen, Thi Xuan Trang; Amyot, Marc; Labrecque, Michel
Abstract: A pot experiment was conducted to investigate the effect of diverse plant species (four herbaceous and four woody species) on the labile pool of six metals (Ag, Cu, Pb, Zn, Ni and Se) present in their rhizosphere. After three months of cultivation, concentrations of trace elements (TE) in above and below-ground biomass of each species were determined. The labile and presumably bioavailable fraction of these TE in the rhizosphere as well as key soil parameters (e.g. pH, electrical conductivity (EC), percent of organic matter and dissolved organic carbon (DOC)) were also measured and compared as a function of plant species. The concentration of TE in plant tissues differed among species. In general and as expected, concentrations were higher in root tissues of tested plants than in above-ground tissues. While the labile pool of several TE in the rhizosphere, notably Ag, Ni, and Cu, was significantly and differently affected by the presence of the plants, pH, EC and percentage of organic matter remained unchanged. In contrast, DOC was higher in the rhizosphere of all tested plants than in soil of the control pots without plants. In addition, there was a positive relationship between Ni and Cu availability concentrations, and DOC levels. This suggests that root systems of different species can have a distinct influence on soil DOC and consequently modify the labile pools of Ni and Cu in the rhizosphere. These findings have important implications for plant selection in phytoremediation projects. Highlights: The labile pools of TE, notably Ag, Ni, and Cu, were differently affected by the presence of the plants. Availability of Ni and Cu is related to the level of dissolved organic carbon (DOC) in the soil. Different root systems can have a distinct influence on soil DOC, and thus can modify the labile pools of Ni and Cu.